UJI PILIH MAKANAN RAYAP KAYU KERING CRYPTOTERMES CYNOCEPHALUS LIGHT - Ginuk Sumarni; Agus Ismanto (Jurnal Penelitian Hasil Hutan, 1989)
The experiment was carried out to study the role of lignin as dry wood termite Cryptotermes cynocephalus Light food. The C. cynocephalus termite was given lignin and cellulose food, separately or both in the test petridish.These research conclude that :1. C. cynocephalus termite besides eating cellulose as main food also eating lignin.2. The survival of C. cynocphalus termite was not influenced by the kind of food i.e. cellulose or lignin.3. The feeding activity of C. cynocephalus termite was highly influenced by the kind of food. The highly feeding activity of C. cynoceph alus was cellulose.4. C. cynocephalus termite prefers the cellulose than lignin,